Woody Species Diversity, Structure, and Regeneration Status of Yemrehane Kirstos Church Forest of Lasta Woreda, North Wollo Zone, Amhara Region, Ethiopia - Amanuel Ayanaw Abunie; Gemedo Dalle (International Journal of Forestry Research)
This study is aimed at generating data on woody species diversity, structure, and regeneration status of some species and was conducted in Yemrehane Kirstos Church Forest of Lasta Woreda, North Wollo Zone, Amhara Region, Ethiopia. Six transect lines were laid following altitudinal gradient. Quadrats of size 20 m × 20 m (400m2) were used to collect data that were established systematically at every 100 m interval along the transect lines. Data on woody species was collected from a total of 34 sampling quadrats of 400m2. To collect data on seedlings and saplings, five subplots of 1 m × 1m (1m2) size located at the four corners and centre of the main plot were used. Species diversity was determined using the Shannon-Wiener index (H′). A total of 39 woody species belonging to 38 genera and 29 families were identified in Yemrehane Kirstos Church Forest. The overall Shannon-Wiener diversity index (H′) and evenness values for the entire forest were 2.88 and 0.79, respectively. The six most abundant woody species in their order of highest density were Juniperus procera, Olea europaea subsp. cuspidata, Maytenus arbutifolia, Osyris quadripartita, Calpurnia aurea, and Debregeasia saeneb. The densities for mature woody species, saplings, and seedlings were 506.6, 514.7, and 415.4 individuals ha−1, respectively. The basal area of the forest is 72 m2 ha−1. The population structure and regeneration status of the forest indicated that there have been high forest degradation and severe anthropogenic disturbances in the area and, therefore, conservation of species, ecosystem restoration, and sustainable use of the forest genetic resources are recommended as a result of this study.